2009
DOI: 10.1093/ndt/gfp482
|View full text |Cite
|
Sign up to set email alerts
|

First and subsequent nonmelanoma skin cancers: incidence and predictors in a population of New Zealand renal transplant recipients

Abstract: Background. Renal transplant recipients (RTRs) have an increased risk of developing nonmelanoma skin cancers (NMSCs). The aims of this study were to determine the incidence and subsequent history of NMSCs in RTRs, together with risk factors. 14.2, 22.9) from transplant, as estimated by survival analysis. Individual predictors of first NMSC in RTRs were older age at first transplant (P < 0.0001), male sex (P = 0.006) and initial immunosuppression regimen (P = 0.001); only age (P < 0.0001) and male gender (P = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 50 publications
(88 reference statements)
5
46
0
Order By: Relevance
“…The 3-year risks of 59% of NMSC and 62% of subsequent SCC in our study are comparable with the risks of 60% of NMSC in New Zealand (11) and 52% of SCC in France (12), and the 5-year risks of 72% of NMSC and 75% of SCC in our study are comparable with the risks of 80% of NMSC in New Zealand (11) and 67% of SCC in France (12). The risk of subsequent SCC in KTR is much higher compared with the general population, in which a 3-year cumulative risk of subsequent SCC of only 18% was calculated (14).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The 3-year risks of 59% of NMSC and 62% of subsequent SCC in our study are comparable with the risks of 60% of NMSC in New Zealand (11) and 52% of SCC in France (12), and the 5-year risks of 72% of NMSC and 75% of SCC in our study are comparable with the risks of 80% of NMSC in New Zealand (11) and 67% of SCC in France (12). The risk of subsequent SCC in KTR is much higher compared with the general population, in which a 3-year cumulative risk of subsequent SCC of only 18% was calculated (14).…”
Section: Discussionsupporting
confidence: 81%
“…A recent study in New Zealand showed that virtually all 96 KTR with skin cancer developed multiple NMSC. After 1 year approximately 30%, after 2 years 50%, after 3 years 60% and after 5 years 80% had developed subsequent NMSC after the first skin cancer (11). Compared with the general population, these percentages are high, because the 3-year cumulative risk of a subsequent SCC after a first SCC in the general population is 18% (14).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…9 Unlike in the general population, squamous cell skin cancers can be quite aggressive in transplant recipients, with a high recurrence rate, metastasis, and death. [10][11][12] Reduction in the incidence and complications associated with malignancy would be a major advance for kidney transplant recipients.…”
Section: Introductionmentioning
confidence: 99%